Properties of the crystalline silicon strained via cavitation impact - Savkina, R.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Properties of crystalline silicon under acoustic cavitation have been investigated. The cavitation impact was initiated by focusing a high-frequency (1– 6 MHz) acoustic wave in liquid nitrogen. AFM, optical and scanning electron microscopy methods as well as energy dispersive X-ray spectroscopy were used to analyze morphology and chemical composition of semiconductor surface. Surface structurization and chemical transformations induced at the solid-liquid interface was observed. The XRD investigation pointed to stresses in the semiconductor lattice induced by the cavitation effect. A standard procedure of photoresponse spectroscopy was employed prior to and after sonication and pointed to an essential photosensitivity rise of the silicon target. The mechanisms involved during Si sonication have been discussed.